Inverse dispersal patterns in a group of ant parasitoids (Hymenoptera: Eucharitidae: Oraseminae) and their ant hosts. (9th June 2019) - Baker, Austin J.; Heraty, John M.; Mottern, Jason; Zhang, Junxia; Hines, Heather M.; Lemmon, Alan R.; Lemmon, Emily Moriarty
Abstract: When postulating evolutionary hypotheses for diverse groups of taxa using molecular data, there is a tradeoff between sampling large numbers of taxa with a few Sanger‐sequenced genes or sampling fewer taxa with hundreds to thousands of next‐generation‐sequenced genes. High taxon sampling enables the testing of evolutionary hypotheses that are sensitive to sampling bias (i.e. dating, biogeography and diversification analyses), whereas high character sampling improves resolution of critical nodes. In a group of ant parasitoids (Hymenoptera: Eucharitidae: Oraseminae), we analyse both of these types of datasets independently (203 taxa with five Sanger loci, 92 taxa with 348 anchored hybrid enrichment loci) and in combination (229 taxa, 353 loci) to explore divergence dating, biogeography, host relationships and differential rates of diversification. Oraseminae specialize as parasitoids of the immature stages of ants in the subfamily Myrmicinae (Hymenoptera: Formicidae), with ants in the genus Pheidole being their most common and presumed ancestral host. A general assumption is that the distribution of the parasite must be limited by any range contraction or expansion of its host. Recent studies support a single New World to Old World dispersal pattern for Pheidole at c . 11–27 Ma. Using multiple phylogenetic inference methods (parsimony, maximum likelihood, dated Bayesian and coalescent analyses), we provide a robust phylogeny showing that Oraseminae dispersed in the opposite direction, from Old World to New World, c . 24–33 Ma, which implies that they existed in the Old World before their presumed ancestral hosts. Their dispersal into the New World appears to have promoted an increased diversification rate. Both the host and parasitoid show single unidirectional dispersals in accordance with the presence of the Beringian Land Bridge during the Oligocene, a time when the changing northern climate probably limited the dispersal ability of such tropically adapted groups. Abstract : The phylogeny of Oraseminae (Eucharitidae) is analysed under multiple phylogenetic frameworks with the most comprehensively sampled molecular dataset for this group to understand their biogeography and evolutionary history. Oraseminae originated in the Old World, but their probable ancestral hosts, the ant genus Pheidole, originated in the New World, and these taxa dispersed in opposite directions. Combining partially overlapping Sanger‐ and Illumina‐sequenced datasets can increase backbone support from character‐rich data while the dense taxon sampling improves the resolution of phylogenetic comparative methods.